2018
DOI: 10.3390/ijerph15020382
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Gender-Specific Influencing Factors of Hypertension among Chinese Adults: A Cross-Sectional Survey Study in Nanchang, China

Abstract: Hypertension has become the leading cause of death worldwide; data on hypertension among Nanchang adults are sparse. The aim of this study was to investigate the prevalence and gender-specific influencing factors of hypertension in adults in Nanchang, China. A cross-sectional survey was conducted with a representative sample of 2722 Chinese residents aged 18 years and above between May and September 2016, with a response rate of 92.4% (2516/2722). A stratified cluster sampling method was adopted in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 28 publications
6
6
0
Order By: Relevance
“…The results of this study also show that women are more likely to have better skills in diet and risk factor management. The findings are consistent with those of Choi et al 85 and Zhou et al 86 who report that women with hypertension have higher diet management skills, especially related to the daily consumption of fresh vegetables and fruits, which are thought to be protective factors associated with better BP control 86…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study also show that women are more likely to have better skills in diet and risk factor management. The findings are consistent with those of Choi et al 85 and Zhou et al 86 who report that women with hypertension have higher diet management skills, especially related to the daily consumption of fresh vegetables and fruits, which are thought to be protective factors associated with better BP control 86…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of hypertension among ISSNHL patients was 22.7%, which was a little higher than that of the local population (19.8%) 23 . Moreover, the DM prevalence in ISSNHL patients in our study was 5.5%, which is lower than recently reported data in literature (9.7%) 24 .…”
Section: Discussionmentioning
confidence: 64%
“…Although the effects of age, overweight, alcohol consumption, and tobacco use on hypertension are well documented at the individual level [2,3,4,5,6,7,8,9,10,11,48], their effects on hypertension has not been investigated yet at regional levels. Our study found that the spatio-temporal variation of hypertension risk was also associated with age, overweight, alcohol consumption, and tobacco use at regional levels.…”
Section: Discussionmentioning
confidence: 99%
“…So far, research has identified risk factors for hypertension at the individual level [2,3,4,5,6,7]. However, less attention has been paid to gender-specific hypertension risk [8,9,10,11]. Moreover, traditional statistical methods used in hypertension research, such as logistic regression, Poisson regression, the Chi-Square test often failed to utilize the participants’ spatial or temporal information [2,3,4,5,6,7,8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation